ESAT-6 Targeting to DEC205+ Antigen Presenting Cells Induces Specific-T Cell Responses against ESAT-6 and Reduces Pulmonary Infection with Virulent Mycobacterium tuberculosis. - Aarón Silva-Sánchez (PLoS ONE, 2015)
Airways infection with Mycobacterium tuberculosis (Mtb) is contained mostly by T cell responses, however, Mtb has developed evasion mechanisms which affect antigen presenting cell (APC) maturation/recruitment delaying the onset of Ag-specific T cell responses. Hypothetically, bypassing the natural infection routes by delivering antigens directly to APCs may overcome the pathogen's naturally evolved evasion mechanisms, thus facilitating the induction of protective immune responses. We generated a murine monoclonal fusion antibody (α-DEC-ESAT) to deliver Early Secretory Antigen Target (ESAT)-6 directly to DEC205+ APCs and to assess its in vivo effects on protection associated responses (IFN-γ production, in vivo CTL killing, and pulmonary mycobacterial load). Treatment with α-DEC-ESAT alone induced ESAT-6-specific IFN-γ producing CD4+ T cells and prime-boost immunization prior to Mtb infection resulted in early influx (d14 post-infection) and increased IFN-γ+ production by specific T cells in the lungs, compared to scarce IFN-γ production in control mice. In vivo CTL killing was quantified in relevant tissues upon transferring target cells loaded with mycobacterial antigens. During infection, α-DEC-ESAT-treated mice showed increased target cell killing in the lungs, where histology revealed cellular infiltrate and considerably reduced bacterial burden. Targeting the mycobacterial antigen ESAT-6 to DEC205+ APCs before infection expands specific T cell clones responsible for early T cell responses (IFN-γ production and CTL activity) and substantially reduces lung bacterial burden. Delivering mycobacterial antigens directly to APCs provides a unique approach to study in vivo the role of APCs and specific T cell responses to assess their potential anti-mycobacterial functions.